Monitoring and Controlling Carbon Dioxide Emission from Vehicles - P.Tamilarasu, Dr.R.Shivakumar, Dr.K.Jaiganesh, M.Senthil Kumar, Dr.T.Logeswaran#5 (International Journal of Advanced Science and Technology, 2020)
The usage of two wheelers and four wheelers are increasing day by day and this leads to more emissions being let out from the vehicles. The polluted gases like carbon-dioxide (CO2), Carbon monoxide (CO) and nitrous oxide are the main contributors for damaging the natural environment. This paper provides an effective and new solution to the pollution problem created by vehicles. The proposed technique involves collecting the emitted CO2 in a chamber containing NaOH aqueous solution fitted in the vehicle to undergo effective chemical reaction. The reactions will produce Na2CO3 thereby the emission levels of carbon -dioxide will be highly reduced. Hardware experimental setup was developed to execute the proposed technique in real time vehicles and satisfactory results were obtained. Keywords: methane, hydro fluorocarbons, air conditioners, aqueous solution, NaOH